2006
DOI: 10.1111/j.1537-2995.2006.00740.x
|View full text |Cite
|
Sign up to set email alerts
|

A weak blood group A phenotype caused by a translation‐initiator mutation in the ABO gene

Abstract: The donor's weak blood group A phenotype most likely resulted from expression of an N-truncated A transferase triggered by alternative translation start sites in the transmembrane domain or stem region.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
46
1
3

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 39 publications
(54 citation statements)
references
References 24 publications
4
46
1
3
Order By: Relevance
“…Since then, different causes of variant expression of ABO glycosyltransferases with reduced activity or dual specificity have been identified. In most cases where a genetic correlate was found, the weak A and B blood group phenotypes were associated with single‐ or multiple‐nucleotide mutations within the part of the ABO gene sequence that encodes for the catalytically active C‐terminal domain 2‐6 . Depending on the location of the resulting amino acid changes, various changes in the activity and/or specificity of A and B transferases in the variant ABO phenotypes may occur.…”
mentioning
confidence: 99%
“…Since then, different causes of variant expression of ABO glycosyltransferases with reduced activity or dual specificity have been identified. In most cases where a genetic correlate was found, the weak A and B blood group phenotypes were associated with single‐ or multiple‐nucleotide mutations within the part of the ABO gene sequence that encodes for the catalytically active C‐terminal domain 2‐6 . Depending on the location of the resulting amino acid changes, various changes in the activity and/or specificity of A and B transferases in the variant ABO phenotypes may occur.…”
mentioning
confidence: 99%
“…One could easily imagine that changes in the amino acid sequence building the catalytic domain can affect the enzymatic activity of the ABO transferase. Phenotype‐genotype correlation studies in individuals with variant ABO blood groups and in vitro expression studies, however, have shown that mutations outside the catalytic domain are also associated with reduced enzyme function and the consequent development of weak A or B phenotypes 6,7,12,13 . Regarding the functional relevance of having amino acid exchanges located far from the enzymatically active site of the protein, these exchanges might affect protein folding, resulting in significant alteration of the shape or orientation of the enzyme's catalytic domain.…”
Section: Discussionmentioning
confidence: 99%
“…We recently demonstrated that amino acid changes outside the catalytic domain can also result in weak A and B antigen expression 6 . Moreover, our studies on alternative downstream start sites of the ABO transcript suggested that weak ABO phenotypes may be based on decreased stability of truncated transcript(s), on less effective translation initiation at the alternative start sites, or on posttranslational effects, such as dislocation of ABO transferase due to missing signal sequences of the membrane‐spanning domain 7 . This study provides experimental evidence that aberrant trafficking of variant A and B transferases can be involved in the formation of weak ABO phenotypes.…”
mentioning
confidence: 91%
“…In addition, the complexity of some blood systems whose antigens may interact closely with other proteins, such as in the Rh complex [14,15], makes the choice of cell line crucial since some are incapable of forming the studied protein network [8,13,15]. Thus, for study or production of human blood group antigen, many reports describe the use of heterologous systems including transfected human embryonic kidney epithelial cells 293 [16], HeLa cells [17], A431 cells derived from human epidermoid carcinoma [18], CHO hamster cells [19], COS monkey cells [13,20], Mouse Erythroleukemic Line (MEL) [15,21], and NS-0 line from myeloma [22], Xenopus laevis oocytes [23], yeast cells [23,24], and Escherichia coli [25]. With regard to these models, it should also be noted that the expression of certain antigens is not limited to erythroid cells so that the absence of native expression may be determinant factor in choosing human heterologous cell lines [13].…”
Section: Cell Targets and Toolsmentioning
confidence: 99%